High performance DC/DC buck converter using sliding mode controller - Al-Qaisi, Mustafa Abbas Fadel; Shehab, Mohanad A.; Al-Gizi, Ammar; Al-Saadi, Mohammed (International Journal of Power Electronics and Drive Systems (IJPEDS), 2019)
This paper investigated the performance of the sliding mode control technique for dc/dc converter using frequency response method. The applications of the step down type switching regulator) buck converter (are found in the devices that use batteries as power source like laptop, cell phones, electric vehicle, and recently, it  has also been used in the renewable energy processing, as a maximum output power can be achieved at higher efficiency. In order to optimize the efficiency and for convenient power management, the issues like power on transients, the effect of load variation, Switching and Electromagnetic interference (EMI) losses has to be overcome for which controllers are used. In the proposed method, pulse width modulation (PWM) based on proportional-integral-derivative sliding mode voltage controller (PID SMVC) is designed for a buck converter and the response for appropriate control parameters has been obtained. The system stability has been examined and analyzed from the performance characteristics, which shows clearly that the buck converter controlled by the sliding mode controller has fast dynamic response and it’s very efficient for various applications.